2006
DOI: 10.1007/s00216-006-0910-7
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform infrared imaging and MR microscopy studies detect compositional and structural changes in cartilage in a rabbit model of osteoarthritis

Abstract: Assessment of subtle changes in the primary macromolecular components of cartilage, proteoglycan (PG) and collagen, is critical for the diagnosis of early stages of osteoarthritis (OA), but to date has remained a challenge. In the current study, we induced osteoarthritic cartilage changes in a rabbit model via ligament transection and medial meniscectomy and monitored disease progression with the techniques of infrared fiber optic probe (IFOP) spectroscopy, Fourier transform infrared imaging spectroscopy (FT-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 59 publications
5
73
2
Order By: Relevance
“…Decrease in the collagen integrity was detected in arthritic human tibial AC as compared to visually normal ones in the first infrared fiber optic probe study (63). Later, infrared fiber optic probe together with PLS model was used to monitor changes in AC surface after ligament transection and medial menisectomy in rabbit (26). Strong correlations have also been obtained between Infrared fiber optic probe data and histological grading of OA using PLS models (51,64).…”
Section: 448 CMmentioning
confidence: 97%
See 1 more Smart Citation
“…Decrease in the collagen integrity was detected in arthritic human tibial AC as compared to visually normal ones in the first infrared fiber optic probe study (63). Later, infrared fiber optic probe together with PLS model was used to monitor changes in AC surface after ligament transection and medial menisectomy in rabbit (26). Strong correlations have also been obtained between Infrared fiber optic probe data and histological grading of OA using PLS models (51,64).…”
Section: 448 CMmentioning
confidence: 97%
“…Assignments of NIR (80,84) and FTIR (19,39,50) proteoglycans than the native cartilage (20) and focal degenerative lesions in human osteoarthritic AC contained less proteoglycans than the surrounding healthy tissue (24). The univariate methods are easy to implement, and, therefore, they have been applied in many studies (25)(26)(27)(28)(29)(30)(31)(32). Collagen and proteoglycan concentration and collagen integrity maps produced using the univariate parameters in human tibial AC are shown in Figure 2.…”
Section: ¡1mentioning
confidence: 99%
“…However, a multivariate PLS regression model is clearly the most efficient analysis method As a practical example, let us now consider univariate vs multivariate analysis techniques for determination of proteoglycan distribution in articular cartilage tissue. Univariate based solutions for FT-IRIS analyses of spatial proteglycan content in articular cartilage have been used in several studies [30][31][32][33]. We have demonstrated that specificity for cartilage proteoglycans is significantly increased by taking advantage of the increased spectral separation of the second derivative spectroscopy.…”
Section: Quantitative Measurement Of Tissue Constituentsmentioning
confidence: 97%
“…The¯ve OA canines underwent an anterior cruciate ligament (ACL) transection surgery in one of the knee joints up to two years ago, which resulted in a classical arthritis. [18][19][20] The protocols and handling of the animals had been approved by the institutional animal care committees. 21 Upon harvesting, the medial tibias in the knee joints were cut by a table saw with a diamond blade.…”
Section: Sample Preparationmentioning
confidence: 99%